78.7k views
5 votes
Which expression is equivalent to 36x2 - 25?

(18x) + (-5)
(18x)? – (5)
(6x)2 + (-5)
(6x)2 – (5)​

2 Answers

2 votes

Answer: (6x)^2 − (5)^2

Explanation:

edge. 2022 got it right

User Blues Clues
by
4.4k points
4 votes

Answer:

The equivalent expression is: (6x + 5)*(6x - 5)

Explanation:

This expression is called the difference of two squares.

It has the following format:
a^(2) - b^(2)

It is factored as:
a^(2) - b^(2) = (a-b)*(a+b)

In this question:


a^(2) - b^(2) = 36x^(2) - 25

So


a^(2) = 36x^(2), then
a = \sqrt{36x^(2)} = 6x


b^(2) = 25, then
b = √(25) = 5

So

The equivalent expression is: (6x + 5)*(6x - 5)

User Krushna
by
5.1k points